Knowledge, Attitude and Practice of Nurses towards Evidence-Based Practice at Al-Medina, KSA. - Abuhasheesh, mohammad; AbuRuz, Mohannad (Jordan Medical Journal, 2016)
Abstract Background: Evidence-Based Practice (EBP) becomes an important concept that is used by researcher, quality members, policy makers, and healthcare team including nursing staff. When EBP is implemented in clinical setting, it will result in maintaining quality of care,efficient use of resources, improvement of patient care, reduction of costs and length of hospital stay and improvement of patient satisfaction. Evidence-Based Practice is a newly term to be used in Saudi Arabia. Purpose: The aim of this study was to describe nurses’ practice, attitudes, and knowledge about EBP in Saudi Arabia. Methods: This was a cross-sectional correlational descriptive study conducted in Al-Madinah Al-Munawarah city, Saudi Arabia. Three hundred and three nurses answered a 24-item Likert scale questionnaire about the study variables. Data were analyzed by descriptive statistics, a serial of bivariate correlations and multiple regressions. Results: Knowledge toward EBP had the highest mean (4.66 ± 1.16), followed by use of EBP (4.09 ± 1.31), and then Attitudes toward EBP (3.81 ± 1.13). Younger nurses tend to use EBP more than older nurses (r = -0.18, p <0.001), females have more positive attitude toward EBP than males (r = -0.16, p <0.001) and nurses with BSC degree have more positive attitude, knowledge, and use EBP than diploma nurses. Nurses with longer years of experience use EBP less than novice nurses (r = -0.12, p <0.05) Conclusion: This is the first study about EBP in Saudi Arabia. This study provided a basis for future studies about the topic and enhancing the use of EBP in Saudi Arabia. Nurses had a moderate knowledge about EBP, however, their attitude toward EBP is lacking. Keywords: Attitudes, Evidence-Based Practice, Knowledge, Nurses, and Saudi Arabia.